Exactly how has income inequality changed? Patterns of distributional change in core societies - Arthur S. Alderson; Jason Beckfield; François Nielsen (Luxembourg Income Study (LIS), 2005)
The recent resurgence of income inequality in some of the core societies has spawned a wide-ranging debate as to the culprits. Progress in this debate has been complicated by the fact that many of the theories that have been developed to account for the inequality upswing imply radically different patterns of distributional change, while predicting the same outcome in terms of the behavior of standard summary measures (e.g., a rise in the Gini coefficient or in Theil's inequality). Handcock and Morris (1999) have developed methods that allow the analyst to precisely identify patterns of distributional change and a set of summary measures to characterize such changes. These are based on the relative distribution, defined for our purposes as the ratio of the fraction of households in the baseline year to the fraction of households in the comparison year in each decile of the distribution of income. We use the available high-quality data from the Luxemburg Income Study to explore the evolution of household income inequality in sixteen core societies. We describe exactly how inequality grew in some core societies since the late 1960s and discuss the extent to which patterns of distributional change were homogeneous or heterogeneous across the core. We find that 1) rising inequality is generally associated with polarization, rather than upgrading or downgrading alone, 2) among those societies experiencing the largest increases in inequality, upgrading typically takes precedence over downgrading in the course of such polarization, and 3) declining inequality, where it occurs, has been the result of convergence, with the magnitude of the shift from the lower tail to the middle exceeding that of the shift from upper tail to the middle.
Keywords: 330; Einkommensverteilung; Gini-Koeffizient; USA; Schätzung; International; Deutschland; Großbritannien